2003
DOI: 10.26719/2003.9.4.718
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices survey among health care workers and tuberculosis patients in Iraq

Abstract: A cross-sectional study was made of 500 patients and 500 health care workers randomly selected from 250 primary health care centers throughout Iraq to evaluate knowledge, attitudes and practices towards tuberculosis [TB]. Using structured questionnaire interviews, the study showed 64.4% of patients had good knowledge, while 54.8% had negative attitudes and practices towards TB. The 2 most important sources of patient information about TB were physicians and television. Of health care workers, 95.5% had good kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(8 citation statements)
references
References 4 publications
2
4
1
1
Order By: Relevance
“…In our study, knowledge on TB transmission routes was relatively high among healthcare providers from ODs with high childhood TB case detection. This finding is similar to the finding of the study in Iraq [ 18 ] and Nigeria [ 22 ] but higher than other studies [ 19 21 , 23 , 24 ]. Over 80% of healthcare providers from ODs with high childhood TB case detection knew four or more childhood TB signs and symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, knowledge on TB transmission routes was relatively high among healthcare providers from ODs with high childhood TB case detection. This finding is similar to the finding of the study in Iraq [ 18 ] and Nigeria [ 22 ] but higher than other studies [ 19 21 , 23 , 24 ]. Over 80% of healthcare providers from ODs with high childhood TB case detection knew four or more childhood TB signs and symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that knowledge on causes of TB, TB transmission routes, symptoms and signs of childhood TB, characteristics of lymph nodes implying TB, and screening criteria for childhood TB were not significantly different among healthcare providers from the OD groups. Most respondents knew that TB is caused by bacteria, similar to findings from a study in Iraq [ 18 , 19 ] but higher than those in Saudi Arabia [ 20 ] and Vietnam [ 19 ] and lower than a study in Ethiopia [ 21 ]. In our study, knowledge on TB transmission routes was relatively high among healthcare providers from ODs with high childhood TB case detection.…”
Section: Discussionsupporting
confidence: 70%
“…The result of this study showed that the overall knowledge of patients about TB was unsatisfactory, but they have better understand than previous study [15] and lower level of understanding than in Iraq [16] . In this study, 81.3% of patients mentioned bacteria/germs as the cause of tuberculosis.…”
Section: Discussioncontrasting
confidence: 54%
“…While similar KAP surveys have been carried out in neighboring countries ( 17 , 18 ), this descriptive cross-sectional study was the first to measure KAP toward TB among university students in Jordan. Although KAP scores were satisfactory, this study revealed knowledge gaps related to TB transmission and treatment especially in non-healthcare students, additionally, it showed no social stigma around TB, good health seeking behavior, and doubt regarding the use of masks in preventing respiratory disease.…”
Section: Discussionmentioning
confidence: 99%